Human biological variation in sesamoid bone prevalence: the curious case of the fabella. Issue 2 (17th October 2019) - Berthaume, Michael A.; Bull, Anthony M. J.
Abstract: The fabella is a sesamoid bone located in the gastrocnemius behind the lateral femoral condyle. In humans, fabellae are 3.5 times more common today than they were 100 years ago, with prevalence rates varying between and within populations. In particular, fabellae have been assumed to be more common in Asians than non‐Asians, equally common in men and women, potentially more common in older individuals, and bilateral cases (one per knee) appear to be more common than unilateral ones. The roles of genetic and environmental factors in this phenotypic variation have been hypothesized, but not rigorously investigated. Given its clinical and evolutionary significance (i.e. being associated with several knee ailments, causing medical issues on its own, interfering with medical devices, and being less common in humans than in other mammals), it is important comprehensively to understand prevalence rate variation, and the roles of genetics and environmental factors in that variation. To address these questions, we performed a meta‐analysis on data from studies published from 1875 to 2018 to investigate possible variation in sexual dimorphic ( n  = 22 studies, 7911 knees), ontogenetic ( n  = 10 studies, 4391 knees), and global ( n  = 65 studies, 21 626 knees) fabella prevalence rates. In addition, we investigated what proportion of cases are bilateral ( n  = 37 studies, 900 individuals), and among unilateral cases ( n  = 20 studies, 204 individuals), if fabellae are more common in the left or right knee. Our results show that, today, fabellae are 2.47–2.60% more common in men than women, and prevalence rates increase ontogenetically in old age (i.e. 70 years old), implying that fabellae can ossify early (i.e. 12 years old) or late in life. Approximately 72.94% of cases are bilateral, and among unilateral ones, fabellae are equally common in right and left knees. There is marked regional variation in fabella prevalence rates, with rates being highest in Asia, followed by Oceania, South America, Europe, Middle East, and North America, and lowest in Africa. Worldwide, an average of 36.80% of knees has ossified fabellae detectable by dissection. These results imply that, while the ability to form a fabella may be genetically controlled, the mechanisms that trigger fabella ossification may be environmentally controlled. What these environmental factors are, can only be speculated. Abstract : The fabella, a sesamoid bone in the knee, is ~3.5× more common today than 100 years ago. We performed meta‐analyses on prevalence rate studies from 1875–2019, and found (i) fabellae are more common in men, older individuals, and Asian/Oceania populations than women, younger individuals, and North American/African populations (ii) 72.94% of cases are bilateral, and (iii) among unilateral cases, there is anti‐symmetry. This supports the roles both genetics and environment in the fabella phenotype.